A+ Certification All-in-One Exam Guide - Meyers, Michael (New York Osborne/McGraw-Hill, 2002)
For computer professionals looking to secure A+ certification, or simply for those desiring an authoritative reference, the second edition of this guide has extended its coverage to include information on Pentium III technology.
Include Index
Keywords: Computers--Examinations -- Computer technicians -- Examinations